Effects of BST on optical and dielectric properties of Na2O-B2O3-SiO2glasses - Pratthana Intawin (2018)
© 2016 Trans Tech Publications, Switzerland. In this research, the effects of Ba0.7Sr0.3TiO3(BST) on optical and dielectric properties of Na2O-B2O3-SiO2glasses were investigated. From the study, the optically transparent glass from BST system was successfully prepared by using melt-quench method. The composition of BST used in this study are ranging between 20-60 wt.% BST. It was found that the addition of BST enhanced conductivity, but in turn reduced the percentage of transmittance in the glasses. The dielectric constant (∈r) of the BST/Na2O-B2O3-SiO2glasses improved with increasing the content of BST, which in turn plays an important role in controlling the properties of the BST/Na2O-B2O3-SiO2glasses.